(untitled) (Asian Business Research, 2016)
In developing countries, government actively promotes foreign investment in order to adapt the new and latest technology. This leads to greater R&D activities, thus this creates knowledge and technology spillover. In this paper, we look at Korea where the R&D has been the main factor of rapid growth. We study the effects of foreign ownership on technological performance by looking at 756 R&D intensive Korean firms from 1999 to 2009. We look the number of applied and registered patents are dependent variables (as a technological performance) and observe statistically significant and positive correlation with foreign ownership due to three main reasons: (a) knowledge and technology spillover, (b) relatively more risk-taking investment behavior of institutional investors, and (c) cherry-picking strategy of investing in firms that perform well. Furthermore, we also observe the R&D expenditure has a strong and positive correlation with the number of applied and registered patents, and R&D expenditure could serve as a proxy variable for technologically advanced industries. Lastly, we observe that the coefficients increase for applied and registered patents for different technology index sub-groups